A 3D in situ cell counter reveals that breast tumor cell (MDA‐MB‐231) proliferation rate is reduced by the collagen matrix density. (1st March 2015) - Kim, Beum Jun; Zhao, Shuting; Bunaciu, Rodica P.; Yen, Andrew; Wu, Mingming
<x xml:space="preserve">Abstract</x> Many cell types require the biophysical and biochemical cues within the 3D extracellular matrix (ECM) to exhibit their true physiologically relevant behavior. As a result, cell culture platforms have been evolving from traditional 2D petridish plates into 3D biomatrices, and there is a need for developing analytic tools to characterize 3D cell culture. The existing cell counting method, using a hemocytometer or coulter counter, requires that cells are suspended in fluids prior to counting. This poses a challenge for 3D cell culture as cells are embedded in a 3D biomatrix. We use a facile 3D cell counting method that overcomes this limitation and allows for in situ cell counting in a 3D cell culture using equipment that is commonly available in a biology lab. Using a breast tumor cell line, MDA‐MB‐231, as a model system, we demonstrated that MDA‐MB‐231 cells (1) grow slower within a 3D collagen matrix than on a 2D substrate for an extended growth time (a week) with a comparable, initial cell‐to‐cell distance, (2) their cell growth rate decreases with the increase of collagen concentration, showing a linear growth rate rather than an exponential growth rate. Further work using flow cytometry showed that the observed growth rate reduction was consistent with the retardation of the transition to S (synthesis) phase in the cell cycle. This work demonstrates the validity of the 3D cell counting method and the importance of cell–ECM interactions in cell proliferation. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:990–996, 2015